Purinylpyridinylamino-based DFG-in/αC-helix-out B-Raf inhibitors: Applying mutant versus wild-type B-Raf selectivity indices for compound profiling. Issue 10 (15th May 2016) - Liu, Longbin; Lee, Matthew R.; Kim, Joseph L.; Whittington, Douglas A.; Bregman, Howard; Hua, Zihao; Lewis, Richard T.; Martin, Matthew W.; Nishimura, Nobuko; Potashman, Michele; Yang, Kevin; Yi, Shuyan; et al.
Graphical abstract: Abstract: One of the challenges for targeting B-Raf V600E with small molecule inhibitors had been achieving adequate selectivity over the wild-type protein B-Raf WT, as inhibition of the latter has been associated with hyperplasia in normal tissues. Recent studies suggest that B-Raf inhibitors inducing the 'DFG-in/αC-helix-out' conformation (Type IIB) likely will exhibit improved selectivity for B-Raf V600E . To explore this hypothesis, we transformed Type IIA inhibitor (1 ) into a series of Type IIB inhibitors (sulfonamides and sulfamides4 –6 ) and examined the SAR. Three selectivity indices were introduced to facilitate the analyses: the B-Raf V600E /B-Raf WT biochemical ( b S), cellular ( c S) selectivity, and the phospho-ERK activation ( p A). Our data indicates that α-branched sulfonamides and sulfamides show higher selectivities than the linear derivatives. We rationalized this finding based on analysis of structural information from the literature and provided evidence for a monomeric B-Raf-inhibitor complex previously hypothesized to be responsible for the desired B-Raf V600E selectivity.